Influência da obesidade sobre a infecção experimental de Gerbils (Meriones unguiculatus) com Giardia lamblia - Luciana Laranjo Amorim Ventura (2016)
Nowadays, the number of obese people in the world has reached alarming proportions, which has brought so much attention because of the metabolic, immunological and the increased susceptibility to infectious diseases that obesity can trigger. In recent years, the number of studies that seek to clarify the impact of adiposity also in parasitic infections have been increasing. However, there are no studies on the association between obesity and giardiasis, the most frequent parasitic disease in developed countries with a high prevalence in developing countries. As the prevalence of both diseases overlap in many areas, it is important to evaluate if this parasitosis would be influenced by the weaknesses in the immune response of obese hosts. 42 gerbils, males with a mean age of 25 weeks were used, divided into 6 groups with 7 animals each: control (CT), Infected Control for 1 week (CTIN) and Infected Control for 2 weeks (XCTIN), receiving diet with 68%, 7% and 20% of calories from carbohydrates, lipids and proteins, respectively; Obese (OB), Obeso Infected for 1 week (OBIN) and obese Infected for 2 weeks (XOBIN) with diet containing 42%, 37.5% and 20% of calories from carbohydrates, lipids and proteins, respectively. In the 10th week of the experiment, the animals of the groups CTIN, XCTIN, OBIN and XOBIN were orally infected with Giardia lamblia, and remain infected for 7 or 14 days, according to the group, when all animals were euthanized and collected blood, small intestine, adipose tissue, liver, spleen and fecal contents. The animals were weighed weekly using scale. For biochemical evaluation, serum glucose, total protein, albumin, cholesterol and triglycerides were determined by enzymatic assay. Cytokines dosages were performed by ELISA. The determination of liver and fecal lipids was performed as described by Folch et al. The evaluation of oxidative stress was based on the determination of the concentration of thiobarbituric acid reactive substances and the dosage of catalase and superoxide dismutase. For histological analysis, the proximal portion of the small intestine, a fraction of liver and epididymal adipose tissue were collected, fixed and intended for obteaining sections and staining with Hematoxylin & Eosin. The villus height, crypt depth and the total area occupied by fatty liver were calculated using the KS300 software from the Carl Zeiss image analyzer. The results were expressed in mean ± standard error, using the Shapiro-Wilk test to verify the normality of the sample, and analysis of variance, followed by Newman-Keuls or a Dunn's test for comparisons between experimental groups. We used the Prism version 6.0, considering a 5% significance level. It was observed that obese gerbils showed higher body weight, relative weight of adipose tissue and liver, dyslipidemia, increased hepatic deposition of total fat, cholesterol and triglycerides in addition to changed adipokines production, making it a good experimental model for this disease with or without parasitic infection. G.lamblia infection in control animals resulted in intestinal villi and crypts injury, increase submucosal inflammation and increased expression of cytokines in the intestine, especially in the first week of infection. Furthermore, it caused increased inflammation in adipose tissue and lipid deposition in the liver that reestablished the following week. In obese, there was no permanent increase in IL-2, 5 and 6 sufficiently to contain the infection, causing greater damage in the intestine and more oxidative stress in the liver. The OOBIN and XOBIN groups still showed a higher excretion of lipids in feces and XOBIN lower weight and adiposity. Gerbils are effective models for the study of obesity induced by diet. In addition, the diet-induced obesity caused immunological and histological changes in various tissues of gerbils that impaired the containment of the G. lamblia infection.